Group music therapy for severe mental illness: a randomized embedded‐experimental mixed methods study. (21st November 2013) - Grocke, D.; Bloch, S.; Castle, D.; Thompson, G.; Newton, R.; Stewart, S.; Gold, C.
<x xml:space="preserve">Abstract</x> Objective Music therapy is an innovative approach to support people with severe mental illness (SMI). The aim of the study was to determine whether group music therapy (GMT) positively impacted on quality of life (QoL), social enrichment, self‐esteem, spirituality and psychiatric symptoms of participants with SMI and how they experienced the intervention. Method The primary outcome was QoL; secondary measures assessed social enrichment, self‐esteem, spirituality and psychiatric symptoms. The 13‐week intervention comprised singing familiar songs and composing original songs recorded in a professional studio. Qualitative data were generated from focus group interviews and song lyric analysis. Results Ninety‐nine adults (57 female) were recruited, with an initial cohort (n = 75) randomized to either: weekly GMT followed by standard care (SC) or SC followed by GMT. Crossover occurred after 13 weeks. Measures were conducted at baseline, 13, 26 and 39 weeks. A second cohort (n = 24) could not be randomized and were assigned to GMT followed by SC. Intention‐to‐treat analysis showed a significant difference between GMT and SC on QoL and spirituality. This was robust to different assumptions about missing data (listwise deletion, last observation carried forward or multiple imputation). Per‐protocol analysis suggested greater benefit for those receiving more sessions. Focus group interview and song lyric analyses suggested that GMT was enjoyable; self‐esteem was enhanced; participants appreciated therapists and peers; and although challenges were experienced, the programme was recommended to others. Conclusion Group music therapy may enhance QoL and spirituality of persons with SMI.